Urinary Tract Infection in Infants: A Single-Center Clinical Analysis in Southern Taiwan - Jen-Hsi Wu; Yee-Hsuan Chiou; Jenn-Tzong Chang; Hsiao-Ping Wang; Ying-Yao Chen; Kai-Sheng Hsieh (Elsevier, 2012)
This study summarized the epidemiology, etiology, and susceptibility of pathogens to antibiotics, and specific characteristics in infants aged less than 4 months diagnosed with urinary tract infection in the past decade in Taiwan. Methods: The medical charts of patients aged less than 4 months admitted for urinary tract infection to Kaohsiung Veterans General Hospital between January 2001 and December 2009 were retrospectively reviewed. Results: A total of 132 patients, with male predominance (68.9%), were enrolled. The top three pathogens were similar to those identified in previous studies in Taiwan. The most common pathogen, Escherichia coli (85.3%), was resistant to ampicillin (75.9%), followed by sulfamethoxazole/trimethoprim (31.7%), and cefazolin (28.5%). Dimercaptosuccinic acid (DMSA) renal scan revealed 34.5% positive findings, while the vesicoureteral reflux (VUR) rate was 37.8% by direct radionuclide voiding cystography and/or voiding cysto-urethrography. Positive DMSA findings significantly correlated with VUR (p<0.001) and higher C-reactive protein level (p<0.05). Conclusions: E coli was the most common pathogen in the present cohort, and the top three pathogens were similar to those found in general pediatric population in Taiwan. VUR was the most common genitourinary tract anomaly in this age group. Positive DMSA was well correlated with VUR and higher C-reactive protein level.